Freedom to Choose Religious Faith in Malaysia: Judicial Perspectives - Ahmad, Rusniah; Halim, Rohizan; Abdul Rahman, Rohana; Romli, Fariza (Innovare Academics Sciences Pvt. Ltd, 2020)
Fundamental rights in Malaysia enjoys a constitutional protection and has been arguably well-guarded by an independent judiciary. Article 11(1) (a) of the Federal Constitution provides for freedom to choose one’s own faith or religious believe even though not in absolute terms. Existing legal restrictions to the enjoyment of this right has never deterred the courts from its noble duty of scrutinizing executive and ministerial action which has impacted the fundamental rights of the people. The emergence of new technology inevitably demands more attention from the judiciary as fundamental rights widens and comfortably give citizens access to more information and expands their legal awareness to new frontiers. Generally, freedom to choose one’s own religion is a right protected under freedom of religion clause constitutionally provided by countries to its citizen. Whether the right is absolute or qualified depend upon legal background and history of that country. In Malaysia, Article 11 of the Federal Constitution was given numerous interpretations by writers, scholars as well as the judiciary on whether the right is absolute or qualified. This paper analyzes decided cases by the Civil Courts and also the Syariah Court. By analyzing decided cases, the tendency of the courts in interpreting Article 11 and also the nature of rights given to Malaysian Citizens in choosing religious belief could be understood. The situation in Malaysia is different because our legal system comprises the civil law as well as Syariah law applicable only to Muslims. Hence, the hurdle in choosing religious affiliation only applies to Muslims and not for other religious adherence